2006
DOI: 10.1016/j.aca.2005.07.069
|View full text |Cite
|
Sign up to set email alerts
|

Preconcentration and frontal electroelution of amino acids for in-line solid-phase extraction–capillary electrophoresis

Abstract: A new frontal electroelution approach that can be used for the preconcentration of amino acids in in-line solid-phase extraction-capillary electrophoresis (SPE-CE) has been developed. A single capillary was employed featuring a short monolithic SPE column created inside the capillary via photo-initiated, free-radical polymerisation of 3-sulfopropyl methacrylate and butyl methacrylate monomers. A weak electrolyte of dilute H 2 SO 4 , pH 2.9, was found to promote adsorption of the amino acids onto the SPE column… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 23 publications
0
19
0
2
Order By: Relevance
“…In capillaries, there are a number of reports of using a monolith for in-line extraction. Baryla et al [260] used a methacrylic acid monolith for the extraction of propanol, and Schaller et al [261] and Breadmore [262] have used a sulphopropylmethacrylate monolith for the extraction of antidepressants and amino acids, respectively. In all the cases, an increase in sensitivity of several orders of magnitude was obtained.…”
Section: Spementioning
confidence: 98%
“…In capillaries, there are a number of reports of using a monolith for in-line extraction. Baryla et al [260] used a methacrylic acid monolith for the extraction of propanol, and Schaller et al [261] and Breadmore [262] have used a sulphopropylmethacrylate monolith for the extraction of antidepressants and amino acids, respectively. In all the cases, an increase in sensitivity of several orders of magnitude was obtained.…”
Section: Spementioning
confidence: 98%
“…On the other hand, in the in-line SPE-CE approach [5, 27 -34], an SPE microcartridge is inserted near the inlet of the separation capillary; the SPE column is an integrated part of the CE capillary and there is no need for modification of the commercial CE instrumentation. The off-line automatic and inline SPE-CE approaches have been reported for the anal-ysis of standard solutions [24,29,30,32,33] and biological samples [22,23,25,27,28], but only a few studies have been reported for the determination of analytes at trace levels in environmental samples [26,31,34], even that is a very promising field with a lot to explore.…”
Section: Introductionmentioning
confidence: 99%
“…Next to a more sensitive detector, the sensitivity may also be improved by concentration of the analytes prior to the CE separation by chromatographic methods in off-line [6,7], online [8][9][10][11] and in-line [12][13][14][15][16][17][18][19][20] fashions. Off-line preconcentration requires manual handling and is time consuming, while in-and on-line systems can minimize these disadvantages.…”
Section: Introductionmentioning
confidence: 99%